Ukraine blames Russia for cyber attacks. Issue 12 (December 2018) - Unknown
Abstract : At a time of elevated tensions over Russia's seizing of three Ukrainian naval vessels and 24 crew, Ukraine's security service (SBU) has alleged that the country has come under a major cyber attack. And it is blaming Russia.